Marginal misfit of heat-pressed milled wax-pattern and CAD/CAM crowns and its effect on stress distribution in implant-supported rehabilitations - Michele Costa de Oliveira Ribeiro; Raissa Micaella Marcello-Machado; Dimorvan Bordin; Edmara Tatiele Pedroso Bergamo; Rafael Soares Gomes (Universidade Estadual de Campinas, 2021)
Aim: To compare the marginal fit of lithium disilicate CAD/CAM crowns and heat-pressed crowns fabricated using milled wax patterns, and evaluate its effect on stress distribution in implantsupported rehabilitation. Methods: A CAD model of a mandibular first molar was designed, and 16 lithium disilicate crowns (8/group) were obtained. The crown-prosthetic abutment set was evaluated in a scanning electron microscopy. The mean misfit for each group was recorded and evaluated using Student's t-test. For in silico analysis, a virtual cement thickness was designed for the two misfit values found previously, and the CAD model was assembled on an implant-abutment set. A load of 100 N was applied at 30° on the central fossa, and the equivalent stress was calculated for the crown, titanium components, bone, and resin cement layer. Results: The CAD/CAM group presented a significantly (p=0.0068) higher misfit (64.99±18.73 μm) than the heat-pressed group (37.64±15.66 μm). In silico results showed that the heat-pressed group presented a decrease in stress concentration of 61% in the crown and 21% in the cement. In addition, a decrease of 14.5% and an increase of 7.8% in the stress for the prosthetic abutment and implant, respectively, was recorded. For the cortical and cancellous bone, a slight increase in stress occurred with an increase in the cement layer thickness of 5.9% and 5.7%, respectively. Conclusion: The milling of wax patterns for subsequent inclusion and obtaining heat-pressed crowns is an option to obtain restorations with an excellent marginal fit and better stress distribution throughout the implant-abutment set.